Chemotherapy and intensity-modulated radiation therapy for locally advanced pancreatic cancer achieves a high rate of R0 resection*. (4th March 2017) - Huguet, Florence; Hajj, Carla; Winston, Corrine B.; Shi, Weiji; Zhang, Zhigang; Wu, Abraham J.; O'Reilly, Eileen M.; Reidy, Diane L.; Allen, Peter; Goodman, Karyn A.
Abstract: Background: To assess local control, survival and conversion to resectability among locally advanced pancreatic cancer (LAPC) patients treated with induction chemotherapy (ICT) followed by chemoradiotherapy treatment using intensity-modulated radiation therapy (IMRT). Material and methods: Between 2007 and 2012, 134 LAPC patients were treated with ICT followed by IMRT. After chemoradiotherapy, 40 patients received maintenance chemotherapy. Results: With a median follow-up of 20 months, median overall survival (OS) was 23 months. One- and two-year OS was 85% and 47%, respectively. On multivariate analysis, progression of disease after IMRT was associated with worse OS. Cumulative incidence of local failure was 10% at one year and 36% at two years. Twenty-six patients (19%) underwent resection after chemoradiotherapy including 22 patients (85%) with negative margins. On multivariate analysis, response to IMRT was associated with surgery (p = .01). Acute grade 3-4 hematologic and non-hematologic toxicity rates were 26% and 4.5%, respectively. Conclusion: IMRT is safe in patients with LAPC. Patients with non-progressive LAPC after ICT and who received IMRT had high rates of local control and prolonged survival.